Active Site Crowding of Cytochrome P450 3A4 as a Strategy To Alter Its Selectivity. (15th December 2016) - Schiavini, Paolo; Cheong, Kin J.; Moitessier, Nicolas; Auclair, Karine
Abstract: Substrate‐promiscuous enzymes are a promising starting point for the development of versatile biocatalysts. In this study, human cytochrome P450 3A4, known for its ability to metabolise hundreds of drugs, was engineered to alter its regio‐ and stereoselectivity. Rational mutagenesis was used to introduce steric hindrance in a specific manner in the large active site of P450 3A4 and to favour oxidation at a more sterically accessible position on the substrate. Hydroxylation of a synthetic precursor of ( R )‐lisofylline, a compound under investigation for its anti‐inflammatory properties, was chosen as a first proof‐of‐principle application of our protein engineering strategy. In a second example, increasing active site crowding led to an incremental shift in the selectivity of oxidation from an internal double bond to a terminal phenyl group in a derivative of theobromine. The same correlation between crowding and selectivity was found in a final case focused on the hydroxylation of the steroid sex hormone progesterone. Abstract : Substrate‐promiscuous enzyme P450 3A4 was engineered to alter its selectivity. Reducing the volume of its active site (crowding effect) led to a shift in the selectivity towards less‐hindered positions in a series of chosen substrates. Selective hydroxylation of a synthetic precursor of ( R )‐lisofylline, of a derivative of theobromine and of progesterone was achieved.